2002
DOI: 10.1055/s-2002-36759
|View full text |Cite
|
Sign up to set email alerts
|

The History of the Development of the Cerebellar Examination

Abstract: The cerebellar examination evolved from observations of experimental lesions made by neurophysiologists and clinical descriptions of patients with trauma to the cerebellum. At the beginning of the 19th century, neurophysiologists such as Luigi Rolando, Marie-Jean-Pierre Flourens, and John Call Dalton, Jr. ablated portions of the cerebellum of a variety of animals and observed staggering gait, clumsiness, and falling from side to side without loss of strength. They concluded that the cerebellum coordinated volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(97 citation statements)
references
References 11 publications
6
89
0
2
Order By: Relevance
“…The cerebellum is a region of the brain that plays an important role in motor control, and contributes toward coordination, precision, and timing of movements (Fine et al, 2002). Therefore, damage to the cerebellum, as observed in UAC mice, may justify the abnormal motor control, movements, and muscle tone observed in these mice, as well as in hUGT1 mice (Fujiwara et al, 2010;Vogel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellum is a region of the brain that plays an important role in motor control, and contributes toward coordination, precision, and timing of movements (Fine et al, 2002). Therefore, damage to the cerebellum, as observed in UAC mice, may justify the abnormal motor control, movements, and muscle tone observed in these mice, as well as in hUGT1 mice (Fujiwara et al, 2010;Vogel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These toxins may adversely affect the cerebellum directly or as part of a more generalized brain effects (Jomova et al, 2011). Findings from other studies, show that the cerebellar neurodegeneration will lead to lesions of the cerebellum giving rise to signs and symptoms generally called cerebellar syndromes which include muscular hypotonia, intentional tremor, nystagmus, scanning speech and ataxic gait (Fine et al, 2002;Gemma et al, 2007;Wolf et al, 2009). The present study has shown that ascorbic acid has an ameliorative effect on the cerebellum of the experimental animals induced toxicity of the mercury chloride.…”
Section: Discussionmentioning
confidence: 99%
“…It receives input from sensory systems of the spinal cord and from other regions of the brain and integrates them to fine tune motor activity. Patients suffered from cerebellar damage have disorders in fine movement, equilibrium, posture and motor learning [1,2].…”
Section: Introductionmentioning
confidence: 99%